Access to health care by migrants with precarious status during a health crisis: some insights from Portugal - Raposo, Vera Lúcia (Human rights review, 2021)
In March 2020, the Portuguese Government issued a remarkable regulation by which irregular migrants who had previously started the regularization procedure were temporarily regularized and thus allowed full access to all social benefits, including healthcare. The Portuguese constitutional and legal framework is particularly generous regarding the right to healthcare to irregular migrants. Nevertheless, until now, several practical barriers prevented full access to healthcare services provided by the national health service, even in situations in which it was legally granted. This decision is not only remarkable in light of the fulfilling of migrants’ rights to health, as imposed by international commitments assumed by, but also in view of the fight against COVID-19. The decision is grounded both on human rights and in public health reasons. The paper is divided in two main parts. In the first one, it analyzes national State obligations with regard to healthcare provision to migrants in irregular situation. In the second part, it analyzes the Portuguese solution, using this case study to discuss the possible mechanisms to comply with such obligations.